2021
DOI: 10.1186/s13148-021-01026-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of expression of epigenetic molecular factors with DNA methylation and sensitivity to chemotherapeutic agents in cancer cell lines

Abstract: Background Altered DNA methylation patterns play important roles in cancer development and progression. We examined whether expression levels of genes directly or indirectly involved in DNA methylation and demethylation may be associated with response of cancer cell lines to chemotherapy treatment with a variety of antitumor agents. Results We analyzed 72 genes encoding epigenetic factors directly or indirectly involved in DNA methylation and demet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 143 publications
(117 reference statements)
1
19
0
Order By: Relevance
“…8 L). Among these candidate molecular targets, nine were significantly enriched in all three cohorts, and five of them (TP53BP1 [ 25 ], RIPK2 [ 26 ], EHMT2 [ 27 ], IGFBP3 [ 28 ], and HMOX1 [ 29 ]) have been reported to have cancer- and chemoresistance-promoting activities simultaneously. Particularly, although EHMT2, a member of the histone methyltransferase family, was identified in all three cohorts, the transcription level of EHMT2 was significantly higher in the fluorouracil-response group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 L). Among these candidate molecular targets, nine were significantly enriched in all three cohorts, and five of them (TP53BP1 [ 25 ], RIPK2 [ 26 ], EHMT2 [ 27 ], IGFBP3 [ 28 ], and HMOX1 [ 29 ]) have been reported to have cancer- and chemoresistance-promoting activities simultaneously. Particularly, although EHMT2, a member of the histone methyltransferase family, was identified in all three cohorts, the transcription level of EHMT2 was significantly higher in the fluorouracil-response group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the IRF5, in our experiment, its expression is related to cisplatin sensitivity. Previous study showed that ZBTB38 can enhance the response to DNMT inhibitor therapies as a target of DNA methyltransferase inhibitor [ 36 ] as well as it can influence response of cancer cell lines to chemotherapy through involving in diverse epigenetic processes affecting DNA methylation [ 37 ]. However, The biological function of ZBTB38 remains also elusive [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also identified that Cas9 -mediated loss of PALB2 , RAD51, RAD51C, RNASEH2A, XRCC1, and XRCC3 conferred olaparib sensitivity in at least 3 out of 6 cell lines. These results suggest that to some extent the effect of those genes on olaparib sensitivity can be dependent on several factors intrinsic to the cell lines such as genetic and epigenetic backgrounds [ 62 , 63 ], and clinical parameters from the original tumors where the cell lines were established (sampling site and pretreatment) [ 64 ]. Therefore, additional studies are necessary to fully elucidate those dependencies for increased PARPi sensitivity in each gene.…”
Section: Discussionmentioning
confidence: 99%